Fertility Desires, Intentions and Behaviour: A Comparative Analysis of Their Consistency - Rita Freitas; Maria Rita Testa (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2017)
Realisation of childbearing intentions implies couple's dyadic interaction and proceptive behaviour. Studies on childbearing intentions and outcomes have rarely considered non-use of contraception or 'proceptive behaviour' in general as an important mediator of fertility outcomes. The traits-desires-intentions-behaviour theory (Miller and Pasta, 1996; Miller et al., 2004; Miller, 2010) expects proceptive behaviour to be the most accurate predictor of a birth and intentions to be more predictive than desires. We test this theory using longitudinal data from the Generations and Gender Surveys from Austria, France and Bulgaria (2004-2013) and performing logistic regression models on birth outcomes which includes as key explanatory variables different pairwise combinations of desires, intentions and contraceptive (or proceptive) behaviour. The findings show that an individual's intention to have a child predicts the birth of a child better than non-use of contraception, or proceptive behaviour; however, proceptive behaviour is a better predictor of a birth than non-use of contraception. Finally, perception of the partner's agreement on having a child now is less predictive than an individual's intention to have a child within three years. This paper calls for the collection of genuine couple-level data on fertility intentions and behaviour and more refined measures on both contraceptive and proceptive behaviour.
Keywords: 300; Fertility; fertility desires; fertility intentions; proceptive behaviour; contraceptive behaviour